The Frequency Of Hepatitis B In Vaccinated beta Thalassemia Major Children With Multiple Blood Transfusions: Frequency Of Hepatitis B In Vaccinated beta Thalassemia Major Children With Multiple Blood Transfusions - Shohab, Sara; Muntaha, Sidra Tul; Zain, Jawaria; Khan, Jawad Ahmad; Ahmad, Rafiq (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the frequency of hepatitis B in vaccinated thalassemia major children receiving multiple blood transfusions. Methods: A Cross Sectional Study was carried out at Department of Pediatric Medicine, Cantonment General Hospital & Holy Family Hospital Rawalpindi from 26th January 2022 to 26th July, 2022. A total of 245 thalassemia major children undergoing blood transfusion therapy with history of complete EPI vaccination against hepatitis B virus were included in the study. Children were tested for HBV positivity by ELISA. The quantitative variables like age and number of transfusion per month was presented as mean & standard deviation. The qualitative variables like gender, frequency of Hepatitis B were presented as frequency and percentages. Data was entered and analyzed using SPSS version 24. Results: Mean age of patients was 9.56+4.3 years. Males and females were 170(69.4%) and 75(30.6%) respectively. There were 136(55.55%) children with less than 8 transfusions and 109(44.44%) with more than 8 transfusions. HBV was recorded in 8.2% of patients. Conclusion: HBV is common in our population with transfusion dependent beta thalassemia major and is significantly associated with higher number of transfusions.